PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJERIAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Purnama, Titik; Rahayu, Intan; Ratnasari Astuti, Dewi (LP2M Universitas Perjuangan Tasikmalaya, 2025)
The purpose of this study is to determine how managerial and institutional ownership impact the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. In this study, 20 companies were selected as a purposive sample. Quantitative data were used. Secondary data were used as sources. Data collection used documentation and library research. Data analysis methods included hypothesis testing, multiple linear regression, and classical assumptions. All of these techniques were conducted using SPSS version 25. The study found that institutional ownership individually had a positive and significant effect on financial performance, while managerial ownership had a negative and significant effect. Both factors influenced overall financial performance. These findings support the assumptions of agency theory, where ownership mechanisms can reduce agency conflicts and improve the effectiveness of company management. These findings support the agency theory assumption, where ownership mechanisms can reduce agency conflicts and improve company management effectiveness. Keywords: Institutional Ownership, Managerial Ownership, Financial Performance, ROA, Agency Theory, Banking Companies. Keywords: Institutional Ownership, Managerial Ownership, Financial Performance, ROA, Agency Theory, Banking Companies